The prevalence and risk factors of major depressive disorders in gynaecological cancer patients - Tee, Bee Chin; Phang, Cheng Kar; M. Saring, Ahmad Rasidi; Md Noor, Mohd Rushdan; I., Aliyasand; Sidi, Hatta (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Major Depressive Disorder (MDD) in gynaecological cancer patients is a disabling illness with significant mental and physical suffering. Determining the risk factors of MDD in cancer patients enables us to pay more attention to those who are vulnerable and to device effective strategies for prevention, early detection, and treatment. The objective of the study is to determine the prevalence of MDD and its associated risk factors in gynaecological cancer patients at Hospital Sultanah Bahiyah, Alor Star. This is a hospital-based cross-sectional descriptive study of 120 gynaecological cancer patients in Gynae-Oncology Unit in Hospital Sultanah Bahiyah, Alor Star. Mini International Neuropsychiatry Interview (MINI) was used for diagnosis of MDD. Socio-demographic data and clinical variables were collected. MVFSFI (Malay version Female Sexual Function Index) was used to determine sexual dysfunction, and WHOQOL-BREF (World Health Organization – Quality of Life-26) was performed to assess quality of life. The prevalence of MDD in gynaecological cancer patients in the study was 18%. The variables found to be significantly associated with MDD were lack of perceived social support, greater physical pain perception, presence of past psychiatric history, and poorer quality of life. Meanwhile, sexual dysfunction was not associated with MDD. Logistic regression analysis revealed that only the psychological health domain of QOL was significantly associated with MDD, and contributed to 60% of the variation in MDD. The prevalence of MDD in gynaecological cancer patients is higher than those in the general population. In view that MDD can compromise cancer prognosis and patient’s well-being, psychosocial intervention is recommended as a part of multi- disciplinary and comprehensive management of gynaecological cancer.